The Effectiveness of Flashcards Media Strategy in Improving Young Learners’ Vocabulary - Nisa Amalia Rachmadi; A. Muliati; Nur Aeni; Nur Aeni (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2023)
This study aimed to identify the effectiveness of flashcards media strategy in improving young learners’ vocabulary in the 7.2 class of SMPN 30 Makassar as a sample of this study. The method of this study used a quantitative method and a pre-experimental research design. The instrument of this study was a vocabulary test. The given tests to the students were pre-test-post-test vocabulary tests. The tests contained 50 items of each digital and non-digital flashcards, those included 3 association flashcards which were Animal, Fruit, and Transportation. It was formulated in multiple-choice and matching items to find the words or picture meaning, true or false to identify the use of words in a sentence, and essay to write the words correctly. As the result of this study, the first null hypothesis (H01) was rejected and the first alternative hypothesis (Ha1) was accepted, the value of Sig. (2-tailed) P = 0.000 less than α = 0.05 was obtained for both pre-test-post-test of digital and paper flashcards media strategy. Otherwise, the second null hypothesis (H02) was accepted and the second alternative hypothesis (Ha2) was rejected, the value of Sig. (2-tailed) P = 1.000 higher than α = 0.05 was obtained for both post-test-post-test of digital and paper flashcards media strategy. To be concluded, the flashcards media strategy was effective to improve young learners’ vocabulary for both digital and paper flashcards media strategy. Both of them were equally effective to improve young learners’ vocabulary in the 7.2 class of SMPN 30 Makassar.